2013
DOI: 10.1007/s10549-013-2723-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA signatures in hereditary breast cancer

Abstract: This study aims to identify signatures of miR associated with hereditary, BRCA1 or BRCA2 mutation positive breast cancer (BC), and non-hereditary BC, either sporadic (SBC) or non-informative (BRCAX). Moreover, we search for signatures associated with tumor stage, immunohistochemistry and tumor molecular profile. Twenty formalin fixed paraffin embedded (FFPE) BCs, BRCA1, BRCA2, BRCAX and SBC, five per group were studied. Affymetrix platform miRNA v.3.0 was used to perform miR expression analysis. ER, PR, HER2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…2). These miRNAs have previously been shown to be linked to the pathogenesis of HCC and other types of cancer (Chiu et al, 2014, Karakatsanis et al, 2013, Murria Estal et al, 2013, Wang et al, 2012, Wong et al, 2011. Among the six miRNAs examined, the expression levels of four matched the microarray results (p< 0.05), warranting further study using a larger cohort of HCC clinical…”
Section: Mirna Expression Is Altered In Hccmentioning
confidence: 71%
“…2). These miRNAs have previously been shown to be linked to the pathogenesis of HCC and other types of cancer (Chiu et al, 2014, Karakatsanis et al, 2013, Murria Estal et al, 2013, Wang et al, 2012, Wong et al, 2011. Among the six miRNAs examined, the expression levels of four matched the microarray results (p< 0.05), warranting further study using a larger cohort of HCC clinical…”
Section: Mirna Expression Is Altered In Hccmentioning
confidence: 71%
“…In addition, a recent study highlighted that non-BRCA1/2 hereditary BC may be sub-classified using specific miR signatures [27]. Recently, Estal and coworkers suggested that the miR expression profile may facilitate the identification of sporadic BC carrying genetic/epigenetic changes in BRCA genes [28]. Our specific aims in the current study were (A) to identify a miR expression signature that could discriminate between familial and sporadic BC in young patients (≤35 years) who are non-carriers of BRCA1/2 mutations; and (B) to identify candidate target-genes related with the differentially expressed miRs.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs can function as novel tumor suppressors or oncogenes in cancer cells according to their targets. Recently, high-throughput array analyses have clearly demonstrated that miR-4417 is upregulated in many human cancers, such as breast cancer, prostate cancer, and gastrointestinal cancer [13–16]. Keon Uk Park et al reported that miR-4417 was upregulated in HCC tissues compared with non-cancerous liver tissue samples by using a microarray-based genome-wide miRNA analysis [11].…”
Section: Discussionmentioning
confidence: 99%